The Olive Ridley Project (ORP): A successful example of how to engage researchers, conservation practitioners and civil society. (21st September 2021) - Stelfox, Martin; Martin-Cereceda, Mercedes; Vahed, Karim; Hudgins, Jillian; Köhnk, Stephanie; Iqbal, Usman; Shameel, Ibrahim; Hancock, Joana M.; Sweet, Michael
Abstract : page_448 other The Olive Ridley Project (ORP) was set up to protect sea turtles and their habitats. The project was formed in 2013, and it became a registered charity in the UK in 2016. From its inception, ORP took a multidisciplinary approach to achieve its goals. Part of its objectives, and the reason why the charity came to fruition, are related to the issue of olive ridley sea turtle (Lepidochelys olivacea ) entanglement in abandoned, lost or discarded fishing gear (also known as 'ghost gear' or 'ghost nets'), and the search for ghost gear and turtle entanglement 'hot spots' throughout the Indian Ocean. The initial ORP research questions were soon challenged by societal interests to develop inclusive educational programmes in local communities and tourist resorts that could raise awareness about the need for conservation of all sea turtle species. In February 2017, ORP opened the first veterinarian-run, fully equipped Marine Turtle Rescue Centre in the Maldives, bringing together the work of researchers, citizen scientists, volunteers, environmentalists, marine biologists and veterinarians. The present work of ORP sits on a strong and scientifically robust collaborative plan. Current ORP research projects range from sea turtle population analyses, spatial ecology, rehabilitation of injured and sick individuals, epibiont parasite analyses, precise turtle identification through photo-ID research, linking ghost gear to responsible fisheries, and analyses of ghost gear drift patterns. The programme enhances community education and outreach by engaging schoolchildren, organizing workshops, promoting sustainable use of ghost gear waste, and training citizen scientists and local fishing communities. The ORP programme encompasses many principles of research engagement, effectively combining scientific knowledge, education and action. This article explores all stages of the process (from research planning and design, to knowledge exchange and inter- and trans-disciplinary impact assessments), describing the active engagement originated by the ORP page_449 other initiative. A reflective insight into the learning, enrichment and challenges of engaging researchers and community actors is also included, considering the current social and scientific framework.